تنفيذ عقد الوكالة بالأجرة في المعاملات التجارية الرقمية: Execution of Agent Contracts in Return in Digital Trading Transactions - Fadlurrahman Naufal; Isman Isman (Universitas Muhammadiyah Surakarta, 2025)
This article aims to analyze the importance of agent contracts in exchange in trading transactions in the digital age. This study uses a qualitative approach through literature studies as a research method, with data sources consisting of publications and literature references. The type of data used is descriptive data in the form of text and documents taken from published sources. Data is collected by tracing and studying the source of those libraries, while analytical descriptive analysis is used to process the data. The results of the study show that agent contracts in exchange are one type of contract that can be accepted as a sharia solution in trade transactions in the digital era, because it makes it possible to avoid trade transactions that fall into the elements of riba and gharar. An agent-for-reward contract is defined as a power of attorney contract in which a person authorizes another person to perform a specific job or transaction in exchange or an agreed wage. Based on this concept, the existence of rewards or wages related to the payment process in transactions or as compensation for certain work is considered valid in Islamic economics, and does not fall under the category of usury, but is considered a legitimate wage (salary).